Comparison of Clock Test Deficits Between Elderly Patients With Early and Late Onset Depression. (December 2015) - Klein, Lisa; Saur, Ralf; Müller, Stephan; Leyhe, Thomas
To compare clock test deficits in elderly patients with early onset depression (EOD) and late onset depression (LOD), we assessed 32 elderly healthy controls (HCs), 26 patients with EOD, and 27 patients with LOD with the clock drawing test (CDT), clock setting test, clock reading test, and the Tübingen Clock Questionnaire testing semantic memory about clock times. There was no significant difference in depression severity between patients with EOD and LOD. Patients with LOD had significantly lower scores on the CDT than patients with EOD and HCs. Semantic memory impairment concerning minute hand functionality was highly correlated with CDT performance and was significantly different between the EOD and the LOD groups. It can be suggested that significant differences in cognitive impairment severity between patients with EOD and LOD can be detected with CDT. Semantic memory impairment concerning minute hand functionality might affect CDT test results in elderly patients with depression.